Integration of the Khanduri Blang Tradition in Multicultural Learning to Optimize Student Character at the UPTD of State Elementary School 13 Makmur - Nana Suryana; Maisura Maisura; Muhammad Iqbal (Journal of Educational Sciences, 2026)
This study explores the integration of the Khanduri Blang tradition into multicultural learning as a strategy to optimize character education among elementary school students at the UPTD SD Negeri 13 Makmur, Aceh. Using a descriptive qualitative approach, this study aims to understand how local cultural values are embedded in learning practices and how these values contribute to students' character development. Data were collected through participant observation, in-depth interviews with teachers, principals, students, traditional leaders, documentation, and student questionnaires. The results showed that the integration of Khanduri Blang effectively strengthened the main character values, namely religiosity, togetherness, brotherhood, and reciprocal cooperation, with student responses reaching 95%–97% positive agreement. The learning process was implemented contextually and participatory through Teaching, Contextual Learning, and Project-Based Learning, which allowed students to experience cultural values directly through collaborative projects and community involvement. This study also identified supporting factors, such as teacher commitment and community involvement, as well as inhibiting factors, including limited teaching materials and a lack of formal training in multicultural pedagogy. Theoretically, this research strengthens the perspective of multicultural education which places local wisdom as an epistemic foundation for character formation.